2012
DOI: 10.1111/j.1369-1600.2012.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Medications development to treat alcohol dependence: a vision for the next decade

Abstract: More than 76 million people worldwide are estimated to have diagnosable Alcohol Use Disorders (AUDs) (alcohol abuse or dependence), making these disorders a major global health problem. Pharmacotherapy offers promising means for treating AUDs, and significant progress has been made in the past 20 years. The U.S. Food and Drug Administration approved three of the four medications for alcoholism in the last two decades. Unfortunately, these medications do not work for everyone, prompting the need for a personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
196
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 106 publications
(142 reference statements)
1
196
0
1
Order By: Relevance
“…Model-specific covariates are noted in the relevant figure legends. The Kenward-Roger correction (Kenward and Roger, 1997) was used in all models, as the use of this correction is highly recommended in repeated-measures models with more complex covariance structures, especially when there is an unbalanced design (Littell et al, 2006). We note that this correction may result in atypical denominator degrees of freedom compared with traditional repeated-measures models (e.g., denominator degrees of freedom may actually be higher than the number of subjects).…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-specific covariates are noted in the relevant figure legends. The Kenward-Roger correction (Kenward and Roger, 1997) was used in all models, as the use of this correction is highly recommended in repeated-measures models with more complex covariance structures, especially when there is an unbalanced design (Littell et al, 2006). We note that this correction may result in atypical denominator degrees of freedom compared with traditional repeated-measures models (e.g., denominator degrees of freedom may actually be higher than the number of subjects).…”
Section: Statisticsmentioning
confidence: 99%
“…A major objective of alcohol research is therefore to develop medications with an ability to prevent relapse to alcohol use. Preclinical studies have identified several classes of molecules with an ability to block relapse-like behaviors in experimental animals Litten et al, 2012). One of the conclusions that have emerged from this research is that type 1 receptors for corticotropin-releasing factor 1 (CRF1) are key mediators of stress-induced alcohol seeking.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing pharmacotherapy has shown limited efficacy (Anton et al 2006); therefore, further investigation of possible alcohol neurochemical targets could lead to new pharmacological interventions (Heilig & Egli 2006;Litten et al 2012). Alcohol targets components of the mesolimbic dopamine system (Larsson & Engel 2004;Vengeliene et al 2008;Soderpalm, Lof, & Ericson 2009), which is involved in the expression of its reinforcing properties (Adinoff 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One further consequence of excessive alcohol use is that 76 million adults worldwide are alcohol dependent (Rehm et al, 2009). Currently, there are four medications approved by the U.S. Food and Drug Administration (FDA) to treat alcohol dependence: disulfiram, oral naltrexone, a longlasting injectable naltrexone, and acamprosate (Litten et al, 2012). In Europe, nalmefene has been also approved in 2013 (Mann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%